Editorial Commentary: Hip Preservation and Opioids - Harris, Joshua D (Arthroscopy, 2020)
Approximately one-third of patients undergoing arthroscopic hip preservation surgery for femoroacetabular impingement syndrome and labral tears are on preoperative opioid medications. The single most important predictor for prolonged chronic postoperative opioid use is preoperative use. Despite the well-documented high success rates in nonarthritic, nondysplastic individuals undergoing hip arthroscopy, up to half of those individuals on preoperative opioids may still be on opioids at 1 to 2 years of follow-up. Mental wellness disorders (e.g., depression, anxiety, substance abuse) significantly impact both pre- and postoperative pain, function, and activity in nearly all joint and general health outcome measures. Multimodal pain management strategies have shown excellent reduction in perioperative opioid utilization. Intraoperative techniques should strive for comprehensive true hip preservation: labral repair, accurate cam/pincer morphology correction, and routine capsular management. Objective, quantitative pain threshold and pain tolerance measurements may improve treatment decision-making, with better prediction of surgical outcomes. Future personalized health care may use a single individual's mu opioid receptor (OPRM-1 gene) and a number of other genetic markers for pain management to reduce the need for traditional opioid medications. Is opioid-free hip arthroscopy possible? Absolutely. Will the opioid epidemic end? Yes, but we have a lot of work to do.Approximately one-third of patients undergoing arthroscopic hip preservation surgery for femoroacetabular impingement syndrome and labral tears are on preoperative opioid medications. The single most important predictor for prolonged chronic postoperative opioid use is preoperative use. Despite the well-documented high success rates in nonarthritic, nondysplastic individuals undergoing hip arthroscopy, up to half of those individuals on preoperative opioids may still be on opioids at 1 to 2 years of follow-up. Mental wellness disorders (e.g., depression, anxiety, substance abuse) significantly impact both pre- and postoperative pain, function, and activity in nearly all joint and general health outcome measures. Multimodal pain management strategies have shown excellent reduction in perioperative opioid utilization. Intraoperative techniques should strive for comprehensive true hip preservation: labral repair, accurate cam/pincer morphology correction, and routine capsular management. Objective, quantitative pain threshold and pain tolerance measurements may improve treatment decision-making, with better prediction of surgical outcomes. Future personalized health care may use a single individual's mu opioid receptor (OPRM-1 gene) and a number of other genetic markers for pain management to reduce the need for traditional opioid medications. Is opioid-free hip arthroscopy possible? Absolutely. Will the opioid epidemic end? Yes, but we have a lot of work to do.